Efektifitas dosis pupuk organik kotoran sapi dan umur pemotongan terhadap produksi rumput Setaria (Setaria Spachelata) pada tanah berpasir - Maria Erviana Kusuma (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2018)
The aim of this research is to know the effect of dosage of cow manure fertilizer on Setaria production in sandy soil, to know the effect of cutting age on Setaria production in sandy soil and to know interaction of dosage of cow manure fertilizer and cutting age on Setaria production on sandy soil. This research was field experiment using Randomized Block Design with three replications. The treatment design was arranged factorial by two factors, the dose of organic fertilizer of cow manure (P) of three levels of p1 = 10 tons ha-1, p2 = 20 tons ha-1 and p3 = 30 tons ha-1. The second factor is cutting age (U) of three levels, u1 = 30 day cutting age, u2 = 45 days cutting age and u3 = 60 days cutting age. The combination of the two factors resulted in 9 treatment combinations with three replicates as a group to obtain 27 experimental units. The results of this study was the application of cow manure fertilizer independently effect on Setaria production. The cutting age treatment independently affected the plant height, number of tillers and Setaria production. There was no interaction between the application of cow manure fertilizer and cutting age to plant height, number of tillers and Setaria grass production.